The Role of Natural Resources on Moderating the Relationship between Fiscal Decentralization and Corruption: Evidence from Indonesia - Ulum, Akhmad Samsul; Rohman, Abdul; Harto, Puji; Ratmono, Dwi; Ghozali, Imam (International Journal of Energy Economics and Policy, 2018)
This study aims to provide empirical evidences about the influence of fiscal decentralization on the level of corruption in regional governments of district and city in Indonesia and the role of natural resources in that influence. Panel data is used in this study with the observation period from 2008 to 2014 and 514 population from regency and city governments. As many as 433 observations from the final sample was taken based on the purposive sampling method. Meanwhile, the hypothesis testing using PLS-SEM with WarpPLS. The results of the study found out that fiscal decentralization will increase the incidence of corruption in the district and city of regional governments. The second finding is that natural resources will increase the incidence of corruption when the regional autonomy system and fiscal decentralization are applied to local governments. Keywords: Fiscal decentralization, corruption, natural resources JEL Classifications: E62, Q34 DOI: https://doi.org/10.32479/ijeep.7252